Stabilising the Euro Area through unemployment benefits re-insurance scheme - Claveres, Guillaume (OECD Publishing, 2018)
The paper examines the possible design and macroeconomic stabilisation properties of a euro area unemployment benefits re-insurance scheme using annual historical data from 2000 to 2016. The scheme we propose is similar in some aspects to the recent proposals, including the IMF's paper on the central fiscal capacity, while preserving important re-insurance characteristics, such as experience rating and caps on cumulative balances. Counterfactual simulations for individual euro area countries suggest that the scheme, at the cost of average annual contributions of 0.17% of national GDP, could have (i) provided additional macroeconomic stabilisation in the financial crisis of 2009-2013, both at the euro area level and at the level of individual countries hit by the crisis, and (ii) avoided permanent transfers among countries
Keywords: Economics; Euro Area